2006
DOI: 10.1002/bdd.493
|View full text |Cite
|
Sign up to set email alerts
|

Profiling in vitro drug release from subcutaneous implants: a review of current status and potential implications on drug product development

Abstract: This review presents current methods and strategies for studying the release characteristics of drugs from subcutaneous implant dosage forms. Implants are dosage forms that are subcutaneously placed with the aid of surgery or a hypodermic needle, and are designed to release drugs over a prolonged period of time. In most cases, the objective of a release test is to identify sufficiently discriminatory procedures that in turn would provide data to set meaningful specifications. Additional information obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 61 publications
0
57
0
1
Order By: Relevance
“…Although utilization of sink conditions does in fact classify the device type-the most common being time dependent (matrix devices) or time independent (reservoir devices)-it seldom reflects in vivo pharmacokinetics. This and other studies utilizing novel delivery platforms have shown a disparity between in vitro release under sink conditions and in vivo release, particularly for poorly water soluble compounds, which constitute the majority of antiretrovirals being developed as microbicides (20,42). With hydrophobic compounds such as the PYDs, achieving sink conditions requires large volumes of aqueous release medium (up to hundreds of milliliters per day) and/or a high concentration of surfactants or organic solvents to increase the API's solubility in the medium.…”
Section: Discussionmentioning
confidence: 92%
“…Although utilization of sink conditions does in fact classify the device type-the most common being time dependent (matrix devices) or time independent (reservoir devices)-it seldom reflects in vivo pharmacokinetics. This and other studies utilizing novel delivery platforms have shown a disparity between in vitro release under sink conditions and in vivo release, particularly for poorly water soluble compounds, which constitute the majority of antiretrovirals being developed as microbicides (20,42). With hydrophobic compounds such as the PYDs, achieving sink conditions requires large volumes of aqueous release medium (up to hundreds of milliliters per day) and/or a high concentration of surfactants or organic solvents to increase the API's solubility in the medium.…”
Section: Discussionmentioning
confidence: 92%
“…The tremendous release of drug ensures the degradation of polymer that can be seen in release profile in the form of sigmoidal curve. Surfacedegrading approach and bulk-degrading approach are the two subcategories of the degradation-controlled mechanism [23,24]. Further studies are needed to be performed in animals followed by the clinical study to validate the effectiveness of the prepared implants.…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated release for implants and microspheres may be accomplished via modifi cations of temperature, solvent, ionic strength, pH, agitation rate, or the addition of surfactants or enzymes [ 54 ] . However, in each case, such changes could potentially alter the mechanism of drug release.…”
Section: Accelerated Test Conditionsmentioning
confidence: 99%
“…Iyer [ 54 ] provided a list of considerations for the development of product specifi cations and in vitro rest methods. Based upon the discussions provided in this chapter, we can add to that list.…”
Section: Concluding Thoughtsmentioning
confidence: 99%